Elevated Hair Mercury Levels Are Associated With Neurodevelopmental Deficits in Children Living Near Artisanal and Small‐Scale Gold Mining in Peru. (21st May 2020) - Reuben, Aaron; Frischtak, Helena; Berky, Axel; Ortiz, Ernesto J.; Morales, Ana Maria; Hsu‐Kim, Heileen; Pendergast, Laura L.; Pan, William K.
Abstract: Children living near artisanal and small‐scale gold mining (ASGM) are at risk of exposure to mercury, a neurotoxicant. It is not certain whether such exposures are harming development, as they occur in underresourced contexts entwined with other stressors, such as malnutrition and enteric infection. This study sought to investigate the association between hair‐mercury levels and visual‐motor, cognitive, and physical development among children living near ASGM in the Peruvian Amazon. Total hair‐mercury levels were measured in 164 children ages 5–12 living in Madre de Dios, Peru. Primary outcomes included Visual‐Motor Integration assessed via the Beery‐VMI Developmental Test, General Cognitive Ability assessed via the Batería‐III Woodcock‐Munoz (Spanish‐language Woodcock‐Johnson Tests of Cognitive Abilities), and Physical Health assessed via anthropometry/hemoglobin counts. Mean (SD) hair‐mercury level was 2.06 (2.43) μg/g. Fifty‐four children (32.9%) had hair‐mercury levels above the World Health Organization reference level of 2.0 μg/g. After controlling for sex, child age, maternal education, and family socioeconomic status, each one unit increase in log hair‐mercury level was associated with a 1.01 unit decrease in Visual‐Motor Integration (95%CI: −2.06, 0.05, p = 0.061), a 2.59 unit decrease in General Cognitive Ability (95%CI: −4.52, −0.66, p = 0.012), and a 2.43 unit decrease in Physical Health (95%CI: −5.34, 0.49, p = 0.096). After adjustment for covariates, children with hair‐mercury levels exceeding the World Health Organization reference level scored 4.68 IQ points lower in Cognitive Ability than their peers. Mercury exposures related to ASGM may be harming child development in the Peruvian Amazon. Children in this region may benefit from intervention to reach their full developmental potential. Key Points: Children living near artisanal and small‐scale gold mining in the Peruvian Amazon are exposed to mercury, a neurotoxicant Children with higher hair‐mercury levels demonstrated significantly lower General Cognitive Ability than their peers in this rural, low‐income context Children living near artisanal and small‐scale gold mining in Peru may benefit from intervention to reach their full developmental potential